Pengaruh Kondisi Proses Terhadap Karakteristik Pulp Pada Fraksinasi Rumput Gajah Menggunakan Asam Formiat - Dizikri, Dizikri; Helwani, Zuchra; Rionaldo, Hari; Zulfansyah, Zulfansyah (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Elephant grass is a lignocellulosic biomass which has not been utilized optimally. Fractination of elephant grass can be converted into valuable products, such as pulp. The objectives on this research is to study the effect of the process condition on pulp yield, cellulose and lignin content in pulp. The effect of process condition were studied by Response Surface Methodology (RSM) using Central Composite Design (CCD). Fractionation of elephant grass performed on a normal boiling point of the solution with a concentration of formic acid (60%, 70% and 80%), the reaction time of 60-180 minutes, solid to liquid ratio of 10/1 to 20/1, 40 grams elephant grass, HCl catalyst 0.1% wt. This research has 4 stages process that are cooking, screening, washing and drying. The pulp from process will be analyzed for yield pulp, alpha celluose content and lignin content. The result shows that fractionation of elephant grass have yield pulp of 53.6% to 73.7%, cellulose pulp of 84.03% to 93.97% and lignin pulp of 11% to 19.5%. the concentration of formic acid and reaction time influence each response significantly.Keywords: biomass fractionantion, central composite design, elephant grass, response surface methodology.